#TITLE_ALTERNATIVE# - SARMA SINAGA (NIM 23499030); Pembimbing: Dr.Ir. Senator Nur Bahagia, TUTI
Rural Logistic System is a logistic system which operate in a village and do distribution service for people's need and collect agriculture product for industrial purpose. This system has constructed to help the farmers for getting suitable price of their product or their needs with lower price. This research is related with an issues of developing a model distribution system for agriculture product to industries in some area with distribution warehouse facilities. Minimizing total annual cost of system problem under consideration is analyzed. This model is developed due blur Bahagia (1999) and Liu (1999). The criteria used include number of order quantities of distribution warehouse and logistic center, minimizing the number of vehicles needed and the total travel distance needed to complete the total distribution service with integration system approach and concept of echelon stock. An optimization model is developed for describing this problem. A heuristic is exploited for solving this problem and use computer codes for this heuristic are written in Visual Basic for shorting the processing time of feasible solution. A hipotetical data is given for implementation the proposed approach. The feasible solution has obtained is need a test to know how near it with the optimal solution. Then modified the early data to three scenarios, (1) decreasing shortage cost and opportunity cost, (2) decreasing standar deviation of demand and (3) decreasing mean of demand. The obtained result that the proposed approach can decrease total annual cost about 0,18% for scenario 1, increase total annual cost about 0,16% for scenario 2 and decrease total annual cost about 21,14% for scenario 3.